Manajemen Kepala Sekolah dalam Meningkatkan Profesionalitas Guru di Sekolah Menengah Pertama Islam Terpadu An-Nahl Jambi - Nurhalim Nurhalim; Kemas Imron Rosadi; Tuti indriani (Journal on Education, 2023)
This study discusses the management of school principals in improving teacher professionalism at SMP-IT An-Nahl Jambi. The research is motivated by a discrepancy between theory and what is happening in the field regarding teacher professionalism in schools. Benveniste argues that there are 6 basics called professional teachers, application of skills based on technical knowledge, advanced educational and training requirements, some formal controls on entry to the profession, existence of professional associations, codes of professional conduct, a sense of responsibility for serving the public. So this study discusses the management carried out by the principal in increasing teacher professionalism then the inhibiting and supporting factors as well as the efforts made by the principal in increasing teacher professionalism at school. This research use desciptive qualitative approach. The results of the research found by researchers are the management applied by the principal through the stages of planning, organizing, mobilizing, supervising and providing evaluation. The supporting factors are the dedication of the head who is totally and sincere at work, supporting facilities and infrastructure, having hafiz Quran teachers, and getting support from the Education Office. While the inhibiting factors are inadequate facilities and infrastructure, lack of time for teachers to participate in training and workshops, seniority and recruitment that is not in accordance with the profession. The principal's efforts to improve teacher professionalism at SMPIT An-Nahl Jambi by instilling discipline, holding training and workshops, building partnerships and cooperation, then always conducting work evaluations.